Seahorses under a changing ocean: the impact of warming and acidification on the behaviour and physiology of a poor-swimming bony-armoured fish. (17th March 2015) - Faleiro, Filipa; Baptista, Miguel; Santos, Catarina; Aurélio, Maria L.; Pimentel, Marta; Pegado, Maria Rita; Paula, José Ricardo; Calado, Ricardo; Repolho, Tiago; Rosa, Rui
Abstract : Many seahorse species are already threatened worldwide, and we do not know how they will endure an additional threat as climate change. Our results show that adult seahorses ( Hippocampus guttulatus ) seem to be relatively well prepared to face future changes in ocean temperature, but not the combined effect of warming and acidification. Abstract : Seahorses are currently facing great challenges in the wild, including habitat degradation and overexploitation, and how they will endure additional stress from rapid climate change has yet to be determined. Unlike most fishes, the poor swimming skills of seahorses, along with the ecological and biological constraints of their unique lifestyle, place great weight on their physiological ability to cope with climate changes. In the present study, we evaluate the effects of ocean warming (+4°C) and acidification (ΔpH = −0.5 units) on the physiological and behavioural ecology of adult temperate seahorses, Hippocampus guttulatus . Adult seahorses were found to be relatively well prepared to face future changes in ocean temperature, but not the combined effect of warming and acidification. Seahorse metabolism increased normally with warming, and behavioural and feeding responses were not significantly affected. However, during hypercapnia the seahorses exhibited signs of lethargy (i.e. reduced activity levels) combined with a reduction of feeding and ventilation rates. Nonetheless, metabolic rates were not significantly affected. Future ocean changes, particularly ocean acidification, may further threaten seahorse conservation, turning these charismatic fishes into important flagship species for global climate change issues.